Uso da terra implícito na produção e no comércio brasileiro : uma análise inter-regional de insumo-produto - Aguirre, Marcia Luiza Cruz (2023)
The use of natural resources is essential for the maintenance of life. The land use is one of these resources, as it is necessary for humanity’s development. In Brazil, land plays an important role, where currently land use covers almost 30% of the national territory for agricultural development. However, this distribution historically occurs asymmetrically, concentrating in the peripheral regions of Brazil. The dynamics of land use and land cover became more intense from 2002 with the commodity boom and government economic incentives directed towards the agriculture and livestock sectors, which impacted the expansion of agricultural areas and contributed to the intensification of the deforestation process.The growth of agriculture has affected the performance of other sectors of the Brazilian economy, as well as contributed to the growth of macroeconomic indices in peripheral regions of Brazil. As an empirical research with a structural approach, this article performs an interregional input-output analysis that aims to answer the following question: to what extent and intensity was the implicit (direct and indirect) content of land use incorporated in the production and commercial flows (inter-regional and international) of Brazilian regions in 2011? For this purpose, 67 sectors of the 27 Brazilian regions were analyzed. The objective of this research is to estimate the implicit content of land use is directly and indirectly incorporated in the production and regional trade in Brazil, and to analyze the impacts of the land use embodied in the inter-regional and international bilateral commercial flows. This analysis found that the economic asymmetries of Brazilian regions are reflected in the distribution of land use content in interregional bilateral commercial flows, where the commercial flows of the Southeast macrozone absorb implicit land use content from the rest of Brazil. The peripheral regions of the North macrozone in Brazil are economically dependent on the exploitation of natural resources, and as a result, it was possible to confirm that these regions are the most intense in the country in the export of goods that incorporate land use content.